Makna Simbolis Bahasa Kiasan dalam Antologi Puisi “Selamat Menunaikan Ibadah Puisi” Karya Joko Pinurbo - Eka Yoga Pranata; Irma Arifah; Widi Suharto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the symbolic meaning contained in the use of figurative language in the poetry anthology Selamat Menunaikan Ibadah Puisi by Joko Pinurbo. This study uses a qualitative descriptive approach with a semiotic analysis method as a theoretical basis, which allows researchers to interpret the signs and symbols in the poetic texts in depth. The results of the study show that the figurative language in the poems does not only function as rhetorical decoration or mere linguistic ornamentation, but has a strong and essential symbolic function in conveying hidden messages and the poet's inner emotions. Symbols such as